2022
DOI: 10.1097/mca.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic index of plasma predicts coronary artery disease severity and major adverse cardiac events in absence of conventional risk factors

Abstract: Background Various overlapping risk factors lead to coronary artery disease (CAD). The atherogenic index of plasma (AIP) is a marker for CAD severity and progression. However, little is known about its contribution to the residual risk of CAD observed in the absence of all typical risk factors.Methods A prospective cohort study of 366 Indian patients undergoing coronary computed tomography (CT) angiography and diagnosed with stable CAD. Diabetes, hypertension, hypercholesterolemia, smoking, previous CAD, alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The CONUT score and the CFS best represented nutritional risk and frailty, respectively, and were independently significant in the final model. Other parameters signaling inflammation and dyslipidemia such as hsCRP, neutrophil-lymphocyte ratio, and TG/HDLc ratio were also significant, similar to results from previous studies [29][30][31]. Previous studies comparing different frailty and nutritional measures in various disease conditions also report the superiority of the CFS and CONUT score [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 87%
“…The CONUT score and the CFS best represented nutritional risk and frailty, respectively, and were independently significant in the final model. Other parameters signaling inflammation and dyslipidemia such as hsCRP, neutrophil-lymphocyte ratio, and TG/HDLc ratio were also significant, similar to results from previous studies [29][30][31]. Previous studies comparing different frailty and nutritional measures in various disease conditions also report the superiority of the CFS and CONUT score [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 87%
“…For instance, Mangalesh et.al. found that AIP values were highly associated with both MACE within 3 years and the severity of CAD among patients with established coronary artery disease detected via coronary computed tomography angiography [36]. Moreover, Balci et.…”
Section: Discussionmentioning
confidence: 94%
“…The TG/HDL-C ratio and the hsCRP/albumin ratio were also independent predictors, consistent with previous studies. 40,41 On comparing the predictive ability of SIIRI vs other variables, SIIRI demonstrated the highest area under the curve. The optimal cut-off of SIIRI was 4.3 × 10 5 to predict severe CAD, represented by a SYNTAX score >22.…”
Section: Discussionmentioning
confidence: 99%